PENGARUH PEMBERIAN DOSIS RAGI TAPE (Kapang Amilolitik) TERHADAP PEMBUATAN TAPE PISANG KEPOK - Fauziah K N; kurnia K; Nita A (Jurnal Pangan dan Gizi, 2020)
Indonesia is known as an agrarian country with the majority of its population living as farmers. One of the results of abundant and diverse agriculture is fruits, including bananas. In this study, the banana used was Kepok banana with the aim of finding the best dose of yeast, using the organoleptic test and alcohol test. The method used in the form of a Completely Randomized Design with different yeast doses (0.5;1;1,5;2;2.5 grams) and carried out organoleptic test and alkohol test. The results showed that the tape with a dose of 2.5 grams of yeast had the highest alcohol content and the most favored organoleptic test respondents were treatment 4 with a dose of 2 grams of yeast. The conclusion from this study is that the more yeast doses given the faster the alcohol metabolism.